Detection of class 1 and 2 integrons, extended-spectrum β-lactamases and qnr alleles in enterobacterial isolates from the digestive tract of Intensive Care Unit inpatients - Bado, Inés (2010)
In this study, we searched for extended-spectrum β-lactamases (ESBLs), class 1 and 2 integrons, and qnrA, qnrB and qnrS genes in 56 oxyimino-cephalosporin and/or ciprofloxacin-resistant enterobacterial isolates obtained from the gastrointestinal tract of patients admitted in an Intensive Care Unit in Uruguay. ESBLs were detected in 11 isolates (6 CTX-M-2, 3 CTX-M-9, 1 CTX-M-15 and 1 PER-2). qnr genes and integrons were detected in 5 and 24 isolates, respectively. Eight different antibiotic resistance gene cassettes were found within six different genetic arrangements. Two types of complex class 1 integrons carrying insertion sequence ISCR1 were found, one showing blaCTX-M-2–orf3 and the other qnrA1–ampR. Ten of the thirteen isolates carrying class 2 integrons presented the element IS5 inserted between intI2 and dfrA1, whereas another class 2 integron lacked the internal stop codon usually present in intI2. This is the first report of the occurrence of qnrA, qnrB and blaCTX-M-9 in Uruguay. Dissemination of the different groups of CTX-M enzymes (i.e. groups 1, 2 and 9) appears to be a recent phenomenon in South America.